Energy-Aware Threshold Sensitive Stable Election Protocol (EATSEP) for Wireless Sensor Networks (Journal of Scientific Research, 2022)
In most of the traditional cluster-based hierarchical routing protocols, the cluster head (CH) selection is made on a random basis. As a result, some unlucky sensor nodes (SNs) become dead quickly; thereby, network lifetime reduces drastically. To overcome this problem, in this paper, a new cluster-based routing protocol- Energy-Aware Threshold Sensitive Stable Election Protocol (EATSEP) is presented for wireless sensor networks (WSNs). In the EATSEP protocol, the CH selection is an optimum process where the initial and residual energy of each SNs are considered within a heterogeneous SNs energy environment. Additionally, our proposed EATSEP protocol has managed to reduce long-distance transmission by routing data among CHs to the base station. In our present study, we have simulated the EATSEP protocol through MATLAB to compare its performance with other popular protocols under some well-known performance metrics. The experimental results indicate that the network stability of the EATSEP protocol improves by 80.81, 66.41, and 27.06 %, respectively, compared to the low-energy adaptive clustering hierarchy (LEACH), Stable Election Protocol (SEP), and Threshold Sensitive SEP under a particular setting. In terms of energy consumption and network throughput, the EATSEP is also superior to other protocols.